Agile Software Development: Methodologies and Trends - Alsaqqa, Samar; Sawalha, Samer; Abdel-Nabi, Heba (International journal of interactive mobile technologies, 2020)
Software engineering is a discipline that undergone many improvements that aims to keep up with the new advancements in technologies and the modern business requirements through developing effective approaches to reach the final software product, agile software development is one of these successful approaches. Agile software development is a lightweight approach that was proposed to overcome the convolutional development methods’ limitations and to reduce the overhead and the cost while providing flexibility to adopt the changes in requirements at any stage, this is done by managing the tasks and their coordination through a certain set of values and principles.In this work, a comprehensive review that outlines the main agile values and principles, and states the key differences that distinguish agile methods over the traditional ones are presented. Then a discussion of the most popular agile methodologies; their life cycles, their roles, and their advantages and disadvantages are outlined. The recent state of art trends that adopts agile development especially in cloud computing, big data, and coordination are also explored. And finally, this work highlights how to choose the best suitable agile methodology that must be selected according to the task at hand, how sensitive the product is and the organization structure.